Dissecting the regulation of fructan metabolism in chicory (Cichorium intybus) hairy roots - Kusch, Ute; Greiner, Steffen; Steininger, Heike; Rausch, Thomas (The new phytologist, 2009)
Fifteen per cent of higher plants accumulate fructans. Plant development, nutritional status and stress exposure all affect fructan metabolism, and while fructan biochemistry is well understood, knowledge of its regulation has remained fragmentary. Here, we have explored chicory (Cichorium intybus) hairy root cultures (HRCs) to study the regulation of fructan metabolism in sink tissues in response to environmental cues. In standard medium (SM), HRCs did not accumulate inulin. However, upon transfer to high-carbon (C)/low-nitrogen (N) medium, expression of sucrose:sucrose 1-fructosyltransferase (1-SST) and fructan:fructan 1-fructosyltransferase (1-FFT) was strongly induced and inulin accumulated. Upon return to SM, inulin was degraded, together with a coordinate decline of 1-SST and 1-FFT expression. In HRCs, cold-induced expression of fructan 1-exohydrolases (1-FEH I and IIa) was similar to cold induction in taproots, even in the absence of accumulated inulin. For high-C/low-N induction of 1-SST and 1-FFT, and cold induction of 1-FEH I and IIa, the signaling pathways were addressed. While 1-SST and 1-FFT induction was similarly prevented by inhibitors of Ca2+ signaling, protein kinases and phosphatases, cold induction of 1-FEH I and IIa revealed distinct signaling pathways. In summary, this study has established chicory HRCs as a convenient experimental system with which to study the regulation of fructan active enzyme (FAZY) expression in heterotrophic cells.
Gesehen am 04.05.2017